Orientation growth modulated magnetic-carbon microspheres toward broadband electromagnetic wave absorption. (February 2021) - Wang, Lei; Yu, Xuefeng; Huang, Mengqiu; You, Wenbin; Zeng, Qingwen; Zhang, Jie; Liu, Xianhu; Wang, Min; Che, Renchao
Abstract: Surface magnetic configurations and electromagnetic responding behaviors can be efficiently modulated by controlling the growth of magnetic materials, which has always been a huge challenge. Here, an in situ orientation growth strategy is developed to build a micron scale Fe3 O4 –Fe3 O4 @C heterojunction via applying Kirkendall diffusion to the orientation growth process. Undergoing precipitation and phase transition process, the oriented Fe3 O4 octahedron tightly rooted in anisotropy Fe3 O4 @C body, constructing various magnetic configurations and enhancing stray magnetic field intensity. As-synthesized magnetic-dielectric microspheres exhibited excellent energy conversion capacity toward electromagnetic wave, including strong reflection loss (RL: 40.8 dB, 2.0 mm) and ultra-wide absorption region (∼11.04 GHz, ∼69% of the tested frequency). Essentially, cross-space magnetic coupling enlarges the responding region beyond the material itself and strengthens electromagnetic wave disputation. Local charge density distribution around the grain boundary plays the key role in forming the enhanced interfacial polarization, which is characterized by the off-axis electronic holography. More importantly, the dynamic response mechanism was firstly observed under an applied magnetic field. Changing magnetic configurations induce the rearrangement of magnetic flux distribution, providing the internal magnetic feedback. Above-mentioned dielectric and magnetic properties of Fe3 O4 –Fe3 O4 @C composites make a breakthrough understanding toward the energy conversion mechanisms. Graphical abstract: Oriented Fe3 O4 octahedron tightly rooted in anisotropy Fe3 O4 @C body, constructing unique magnetic-dielectric assembly and enhancing microwave absorption ability. Image 1